Mitotic catastrophe heterogeneity: implications for prognosis and immunotherapy in hepatocellular carcinoma - Mao, Zun; Gao, Zhixiang; Long, Ruyu; Guo, Huimin; Chen, Long; Huan, Sheng; Yin, Guoping (Frontiers in Immunology, 2024)
The mitotic catastrophe (MC) pathway plays an important role in hepatocellular carcinoma (HCC) progression and tumor microenvironment (TME) regulation.However, the mechanisms linking MC heterogeneity to immune evasion and treatment response remain unclear.Based on 94 previously published highly correlated genes for MC, HCC patients' data from the Cancer Genome Atlas (TCGA) and changes in immune signatures and prognostic stratification were studied. Time and spatial-specific differences for MCGs were assessed by single-cell RNA sequencing and spatial transcriptome (ST) analysis.Multiple external databases (GEO, ICGC) were employed to construct an MC-related riskscore model.Identification of two MC-related subtypes in HCC patients from TCGA, with clear differences in immune signatures and prognostic risk stratification. Spatial mapping further associates low MC tumor regions with significant immune escape-related signaling. Nomogram combining MC riskscore and traditional indicators was validated great effect for early prediction of HCC patient outcomes.MC heterogeneity enables immune escape and therapy resistance in HCC. The MC gene signature serves as a reliable prognostic indicator for liver cancer. By revealing clear immune and spatial heterogeneity of HCC, our integrated approach provides contextual therapeutic strategies for optimal clinical decision-making.